INFLUENCE OF GROWTH REGULATORS ON MULTIPLICATIONS OF SUGARCANE (SACCHARUM OFFICINARUM. L) VARIETY CO 6886 - Ogawi Ojwok Bnyawang; Deng , Pio Kur (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Sugarcane (Saccharum officinarum L.) is a member of the genus Saccharum from family Gramineae and is an important agricultural cash crop in tropical and subtropical region of the world. The objective of this study was to evaluate the effect of different concentration of cytokinins (BAP, kinetin and 2iP) and auxins (IBA, and NAA) combinations of different plant growth regulators on the sugarcane cv. Co 6886. Plant material of sugarcane cv. Co 6886 was selected form greenhouse in Plant Tissue Culture Laboratory at Agriculture Research Corporation (ARC) in Sudan. The young meristem cutting explants were inoculated on to sterilized solid basal MS medium (Murashige and Skoog’s, 1962) supplemented with different concentrations of cytokinins BAP (1.0 - 2.5mg/l), kinetin (1.0 - 2.5mg/l) and 2iP (1.0 - 2.5mg/l) and concentration of auxins (IBA (2.0 - 5.0mg/l) and NAA(2.0 – 5.0mg/l) on combinations of different plant growth regulators. Data were collected after two weeks, four weeks and six weeks to evaluate the morphogenesis of shoot-tip explant and evaluate the numbers of roots per explant which have effect on plant growth regulators on the sugarcane cv. Co 6886. Result indicates that the explant generated from shoot-tip was highest on MS medium supplemented with BAP (2.0 – 2.5mg/l), Kinetin (1.0 – 2.5mg/l) and 2iP (2.0 – 2.5mg/l) all of them after two, four and six weeks. While the rooting were observed on MS medium supplemented show the best with the IBA concentrations (5.0mg/l) and NAA (2.0 - 5.0mg/l) after two, four and six weeks.